2014
DOI: 10.1155/2014/708482
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Urban Taxi Drivers’ Activity Distribution Based on GPS Data

Abstract: With the rapid development of information communication technology and data mining technology, we can obtain taxi vehicle’s real time operation status through the large-scale taxi GPS trajectories data and explore the drivers’ activity distribution characteristics. Based on the 204 continuous hours of 3198 taxi vehicles’ operation data of Shenzhen, China, this paper analyzed the urban taxi driver’s activity distribution characteristics from different temporal and spatial levels. In the time level, we identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…In Shenzhen, the peak hour of taxi passenger's is almost at the midnight, such as in TAZ2, TAZ7, and TAZ8, which is similar to the research of Hu et al (2014).…”
Section: Eight Tazs' Passenger Demands' Spatial-temporal Distributionsupporting
confidence: 75%
See 2 more Smart Citations
“…In Shenzhen, the peak hour of taxi passenger's is almost at the midnight, such as in TAZ2, TAZ7, and TAZ8, which is similar to the research of Hu et al (2014).…”
Section: Eight Tazs' Passenger Demands' Spatial-temporal Distributionsupporting
confidence: 75%
“…Each taxi driver's daily activity space area mean center may have the relationship with the centroid of the whole taxi drivers' activity space [19], similar to the Susilo & Kitamura (2005) [30] analysis of the worker's daily activity locations relationship. We can analyze taxi driver's day-to-day variation on activity space and statistically analyze the second moments of activity locations.…”
Section: The Extended Second Moments Of Activity Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Hu et al [2] found that the location in which taxi drivers' cruise and search for the next passenger' pick-up location will be near the previous drop-off location by analyzing the statistical results of the distance between each taxi driver's pick-up locations' mean center and drop-off locations' mean center. Dong et al [5] classified drivers into three groups based on revenue and compared different driver groups in terms of spatiotemporal and strategy aspects.…”
Section: Spatial Pattern Of Taxicabsmentioning
confidence: 99%
“…Cabdrivers' mobility patterns and operating strategies have been widely studied since large-scale taxi GPS trajectories became obtainable due to the rapid development of information and communication technologies (ICT). For example, previous studies analyzed the distance and direction distributions of intraurban trips [1], urban cabdrivers' activity distribution [2], spatial variations in urban taxi ridership [3], cabdrivers' operation strategies with respect to revenue [4,5], and alternative taxi services strategies [6].…”
Section: Introductionmentioning
confidence: 99%